Correction: in vitro and in vivo trypanocidal activity of h2bdtc-loaded solid lipid nanoparticles. - PLOS Neglected Tropical Diseases Staff (Public Library of Science (PLoS), 2015)
[This corrects the article DOI: 10.1371/journal.pntd.0002847.].